Analisis Prosedur Pengendalian Internal Dana Kas Kecil pada Restoran Bakso Mas Gendut Bukit Besar Palembang - Arif Rahmayadi (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to analyze how the internal control process procedures for petty cash funds are applied to Bakso Mas Gendut Restaurant in Palembang City. This research is a qualitative research that obtains data from observations and interviews. The results showed that the restaurant used the Imprest Fund System of bookkeeping. The results of this study also indicate that to record petty cash, Bakso Mas Gendut Restaurant consolidates the input from all accounting journals which constitute a classification of accounts.